Brain SERT Expression of Male Rats Is Reduced by Aging and Increased by Testosterone Restitution. (18th December 2013) - Herrera-Pérez, José Jaime; Fernández-Guasti, Alonso; Martínez-Mota, Lucía
Abstract : In preclinical and clinical studies aging has been associated with a deteriorated response to antidepressant treatment. We hypothesize that such impairment is explained by an age-related decrease in brain serotonin transporter (SERT) expression associated with low testosterone (T) levels. The objectives of this study were to establish (1) if brain SERT expression is reduced by aging and (2) if the SERT expression in middle-aged rats is increased by T-restitution. Intact young rats (3–5 months) and gonad-intact middle-aged rats with or without T-restitution were used. The identification of the brain SERT expression was done by immunofluorescence in prefrontal cortex, lateral septum, hippocampus, and raphe nuclei. An age-dependent reduction of SERT expression was observed in all brain regions examined, while T-restitution recovered the SERT expression only in the dorsal raphe of middle-aged rats. This last action seems relevant since dorsal raphe plays an important role in the antidepressant action of selective serotonin reuptake inhibitors. All data suggest that this mechanism accounts for the T-replacement usefulness to improve the response to antidepressants in the aged population.